PENGARUH PELATIHAN PENGEMBANGAN,GAYA KEPEMIMPINAN, MOTIVASI, TERHADAP KINERJA PEGAWAI (Studi Kasus Dinas Pemuda Olaharaga dan Pariwisata Provinsi Jawa Tengah ) - James Clinton Hutabarat, 14.05.51.0167; Suko Priyono, Bambang (Students' Journal of Economic and Management, 2018)
The purpose of thos study was to determine the effect of Development Training, Leadership style, and Motivation on Emplolyee Performance at the Sports and Tourism Youth Office in Central Java. This study also aims to collectively determine the influence of the three independent variables on the dependent variable and to find out which variable is the most dominant influence between the three independent variables on the dependent variable, this type of research uses qualitative research, with a population of 110 employees. Data collection uses a questionnaire with a Likert scale. The results showed that Development Training had a significant positive effect on performance. Leadership style has a positive not significant effect on employee performance. Motivation has no significant positive effect on employee performance Keywords: Development Training, Leadership Style, Motivation, and Employee Performance